Investigating Errors in Past Simple Tense Usage Among English Language Learners As a Second Language : A Contemporary Analysis - M.R.F Nashfa; MJF Sujani; MB Nowzath; MR. Rishad Muhammed (Penerbit Hellow Pustaka, 2025)
This research aimed to find out the Common Errors Students make in learning past simple tense. The population of this research was Grade 6 students of K / Denu As Siraj Boys College—Dellanga, Gelioya. The objectives of the study were to identify the challenges faced by the grade 6 students, To find out the rules and regulations of the past simple tense, To find out the knowledge of regular and irregular verb forms, and to investigate the improvement in the level of language proficiency of students after examining them. The researcher used a mixed method to collect data from the students. Quantitative and Qualitative methods were used. Post Test and Pre Test were used as the quantitative data and the Interview as the Qualitative method. In this research, 35 students were performed as the sample. After the data collection procedure the researcher analyzed the data according to written test performance. In this process (SST), the Surface Strategy Taxonomy method was used to classify the errors.The findings of this research indicated that there were 130 total errors that students made in Post Test. which were classified into four categories based on the Surface Strategy Taxonomy (SST). Those were the error of omission with 47 errors , error of addition with 19 errors, misformation with 61 errors and misordering with 3 errors. The students made the dominant error in misformation category. It can be seen from the percentage result where misformation was 47%,then followed by error of omission with 36%,errors of addition with 15% and misordering with 2%.On the other hand in Pre Test students committed error in Misformation was 54%, error with omission 38%, Addition 6%, and Misordering 2%. The researcher finally got the conclusion that in both tests most of the students made dominant errors in Misformation. The researcher suggests that students learning English as a second language need proper guidance from the beginning. Emphasis should be placed on speaking practice rather than writing to help them better understand the language. Additionally, they are encouraged to develop reading habits to learn sentence structures and new vocabulary in English.